Evaluating corn distiller's dried grains with solubles as a rumen undegradable protein replacement for soybean meal in Boer-type grower rations - Knobbe, Emily; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2019)
A global increase in goat meat demand reveals a gap in knowledge for US farmers looking to increase profit margins through replacing rumen undegradable protein sources. We investigated whether corn distiller's dried grains with solubles (DDGS) or corn gluten feed (CGF) can be utilized as a lower cost replacement for soybean meal (SBM) in Boer-type grower rations. In our experiment, 75 Boer-type goats (26.9 0.2 kg, approx. 70 d of age) were used in a completely randomized design for 35 d. Goats were assigned to pens based on weight and then pens were randomly assigned to one of 5 experimental diets: 1) 100% SBM, 2) 100% DDGS, 3) 66% DDGS/33% CGF, 4) 33%DDGS/66% CGF and 5) 100% CGF. Pens consisted of 3 goats per pen with 5 pens per treatment. Each wk BW, ADG, ADFI and G:F were measured. Data was analyzed using the GLIMMIX procedure in SAS (v. 9.4, Cary, NC) with pen as the experimental unit and a designate alpha value of 0.05. Our results showed no treatment effect of diet for variables (P<0.05), except for feed cost, measured in dollars/goat for 42 d (P=0.0008). Feed cost ($/goat) was averaged $1.43 less for goats fed CGF or DDGS compared to those fed SBM (P<0.05). Treatments including DDGS or CGF showed a significant (P<0.05) quadratic effect for ADFI, g/d (P=0.038) indicating a feed intake reduction for utilization of both alternative protein sources: 66%DDGS/33%CGF, 33%DDGS/66%CGF, 100% DDDGS, 100% CGF(1,022, 1,074, 1,110 and 1140 respectively.) Therefore, our research shows that DDGS can be effectively utilized with CGF as a lower cost rumen undegradable protein replacement for SBM while maintaining BW, ADG, ADFI, and G:F metrics.
Keywords: Spring 2019